Hippocampus, Time, and Memory – A Retrospective Analysis - Meck, Warren H. (Behav Neurosci, 2013)
In 1984, there was considerable evidence that the hippocampus was important for spatial learning and some evidence that it was also involved in duration discrimination. The article Hippocampus, Time, and Memory (Meck, Church, and Olton, 1984), however, was the first to isolate the effects of hippocampal damage on specific stages of temporal processing. In this review, to celebrate the 30(th) anniversary of Behavioral Neuroscience, we look back on factors that contributed to the long-lasting influence of this article. The major results were that a fimbria-fornix lesion (a) interferes with the ability to retain information in temporal working memory and (b) distorts the content of temporal reference memory, but (c) it did not decrease sensitivity to signal duration. This was the first lesion experiment in which the results were interpreted by a well-developed theory of behavior (scalar timing theory). It has led to extensive research on the role of the hippocampus in temporal processing by many investigators. The most important ones are the development of computational models with plausible neural mechanisms (such as the Striatal Beat-Frequency model of interval timing), the use of multiple behavioral measures of timing, and empirical research on the neural mechanisms of timing and temporal memory using ensemble recording of neurons in prefrontal-striatal-hippocampal circuits.